Fine-scale breeding habitat preferences of southern elephant seals (Mirounga leonina) on península valdés - Retana, Maria Valeria; Guzman, Julia; Lewis, Mirtha Noemi (Aquatic Mammals)
This study analyzed fine-scale habitat selection of southern elephant seals (Mirounga leonina) on Península Valdés, Patagonia, Argentina, during a decade of population stability. The results showed repeatability and consistency in harem formation in a predictable manner and according to specific environmental characteristics. Censuses were conducted during the peak of the breeding seasons (2001 to 2007 and 2010), and ten topographic variables were surveyed along 12 km of coast. The breeding social context was associated with certain topographic variables. Reproductive groups tended to occur in bays sheltered by cliffs with accessible beaches of slope less than 4° and unconsolidated substrates. The nonreproductive groups were found on shelf points. The spatial distribution reported herein will contribute to the understanding of the large-scale distribution of breeding groups on Península Valdés and other breeding colonies of southern elephant seals. Fil: Retana, Maria Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Guzman, Julia. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina